2016
DOI: 10.1038/ijo.2016.20
|View full text |Cite
|
Sign up to set email alerts
|

The varying effects of obesity and morbid obesity on outcomes following cardiac transplantation

Abstract: The purpose of this study was to compare the outcomes of patients undergoing cardiac transplantation stratified by body mass index (BMI, kg m(-)(2)). The Alberta Provincial Project for Outcome Assessment in Coronary Heart Disease registry captured 220 cardiac transplantations in Alberta, Canada from January 2004 to April 2013. All recipients were stratified by BMI into five groups (BMI: <20, 20-24.9, 25-29.9, 30-<34.9 and ⩾35). Patient characteristics were analyzed by analysis of variance and χ(2) analyses. Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
1
14
2
Order By: Relevance
“…Yet, the question of whether overweight and obesity negatively impact post‐HTx clinical outcomes also remains controversial. Most studies focusing on body mass index (BMI) at time of transplant have found an elevated risk for graft loss and mortality in HTx recipients with morbid obesity only (BMI > 35), but not in groups having a low BMI at transplantation . Still, many patients gain weight post‐HTx: one prospective registry study reporting overweight and obesity in, respectively, 37% and 13.6% of patients at 3 years after HTx, which might ultimately elevate the risk for chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the question of whether overweight and obesity negatively impact post‐HTx clinical outcomes also remains controversial. Most studies focusing on body mass index (BMI) at time of transplant have found an elevated risk for graft loss and mortality in HTx recipients with morbid obesity only (BMI > 35), but not in groups having a low BMI at transplantation . Still, many patients gain weight post‐HTx: one prospective registry study reporting overweight and obesity in, respectively, 37% and 13.6% of patients at 3 years after HTx, which might ultimately elevate the risk for chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies reporting on 47 528 recipients transplanted between 1986 and 2014 met our selection criteria [8][9][10][11][12] (Figure 1). …”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Heart transplant is the primary treatment for end-stage HF; however, morbid obesity is a relative contraindication to transplantation [8] . A BMI ≥ 35 kg/m 2 is associated with early complications and decreased long-term survival after heart transplant, compared to class I obesity [2] . Weight loss improves cardiovascular function through increased left ventricular diastolic and systolic function, reduction of myocardial oxygen consumption, and reversal of impaired aortic distensibility [4] .…”
Section: Discussionmentioning
confidence: 98%
“…Heart transplantation is the standard management for advanced HF. However, a body mass index (BMI) ≥ 35 kg/m 2 is associated with increased early complications, decreased longterm survival, and lower likelihood of receiving an organ [2,3] . Weight loss results in decreased vascular stiffness and reduction in ventricular hypertrophy [4] .…”
Section: Introductionmentioning
confidence: 99%